Desain Bodi Sepeda Sepeda Motor Hybrid Tipe Skuter dengan Metode DFMA (Design for Manufacturing and Assembly) - Muhammad Ali Yafi; Andarmadi Jati Abdhi Wasesa (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The rapid development of vehicle technology increases the demand for efficient and manufactured hybrid motorcycle designs. This study designed a scooter-type hybrid motorcycle body with DFMA method for production and assembly efficiency. The study begins with the identification of consumer needs through questionnaires, then converted into measurable specifications using QFD. This specification became the main foundation in the development of the body structure. The results showed that DFMA design provides advantages over those of custom body manufacturers. Although the duration of manufacturing in both methods is the same at five days, differences appear at the assembly stage. DFMA-designed bodies are assembled in 50 minutes, while custom products take 1 hour. Although the time difference is not drastic, the results prove that the implementation of DFMA successfully simplifies the component structure and speeds up the assembly workflow. Thus, the study concludes that the DFMA approach is a relevant strategy for designing hybrid vehicle components to reduce operational costs and increase productivity in automotive manufacturing assembly in the future.